Kidney Stone Epidemiology, Risk Factors, and Ethno-Medical Approaches: A Short Communication - Soni, Sandeep Kumar; Pandey, Rajesh (International Journal of Scientific Research in Biological Sciences, 2024)
Stone isK the dominant problem in the world due to number of factors associated with dietary habits affected to the renal, filtration and urinary systems directly and indirectly, which may causes by the deposition of elements in form of oxalate, silicate, phosphate and uric acid. Stone diseases also concerned with some major elements which comprises secondary and tertiary derivatives which partially or completely affected to concern function organs and its metabolism. Increased incidence in males as compared to females subjects were highly acknowledges. It also has been attributed to increased dietary protein intake, which increases and induced the urinary excretion of phosphates, magnesium and reduces urinary citrate status etc. The treatment of stone disease and concerned complicated factor problems resolves by medicated principles allopathically and homeopathically but the most of the prominent treatments allowed by Ayurveda system. Most of the ethno medicinal and herbal therapy not only declines the ratio of concerned elements but also possess a diverse significant protective response which is reviewed here with updated information. In this review article we are focused on the etiology and epidemiology of kidney stone in population of various age groups with respective gender ratio along with role of diet in kidney stone. The study also illustrates the ethno medical approaches with certain ethno herbal plants which are effectively used for the treatment of kidney stone.